Do tax havens affect financial management? The case of U.S. multinational companies - Alessandro Chiari (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This study examines whether the use of tax haven subsidiaries by U.S. multinational corporations (MNCs) is associated with more intense use of share buybacks and with improvement in management's ability to generating revenues. I find that MNCs' more intensive tax haven subsidiary use is positively associated with a higher management score, a higher buyback ratio, and a higher level of free cash flow. I also find a higher increase in the buyback ratio of U.S. companies following the sales of U.S. stocks from entities located in tax havens. In cross-sectional analyses, I identify channels through which the positive association between tax haven intensity and share buybacks is more pronounced. I also test the share buyback execution of U.S. MNCs affected by recent legislation promulgated in the U.S. (2017 corporate tax cut, 2017 repatriation tax). Our findings reveal a higher sensitivity to this legislation by MNCs with more presence in tax havens.
Keywords: G23; G28; G32; G35; H26; K34; 330; Tax Havens; Subsidiaries; U.S. Multinational Corporations; Share Buybacks